Does Federally-Funded Job Training Work? Nonexperimental Estimates of WIA Training Impacts Using Longitudinal Data on Workers and Firms - Fredrik Andersson; Harry J. Holzer; Julia Lane; David Rosenblum; Jeffrey A. Smith (Institute for the Study of Labor (IZA), 2013)
We study the job training provided under the US Workforce Investment Act (WIA) to adults and dislocated workers in two states. Our substantive contributions center on impacts estimated non-experimentally using administrative data. These impacts compare WIA participants who do and do not receive training. In addition to the usual impacts on earnings and employment, we link our state data to the Longitudinal Employer Household Dynamics (LEHD) data at the U.S. Census Bureau, which allows us to estimate impacts on the characteristics of the firms at which participants find employment. We find moderate positive impacts on employment, earnings and desirable firm characteristics for adults, but not for dislocated workers. Our primary methodological contribution consists of assessing the value of the additional conditioning information provided by the LEHD relative to the data available in state Unemployment Insurance (UI) earnings records. We find that value to be zero.
Keywords: I38; J08; J24; 330; job training; active labor market program; program evaluation; Workforce Investment Act; administrative data; Berufsbildungspolitik; Arbeitsmarktpolitik; Arbeitsmarktpolitik; Wirkungsanalyse; Arbeitsmarktintegration; Beschäftigungseffekt; USA